Analisis Manajemen Inventory Spare Parts Alat Berat Pelabuhan Model Consignment Stock Guna Meminimumkan Total Inventory Cost (TIC) di PT XYZ - Rista Dwi Kusumahati; Wiwin Widiasih (Tekmapro : Journal of Industrial Engineering and Management, 2022)
ABSTRACT PT. XYZ is a service company engaged in the maintenance of port heavy equipment and modification of port heavy equipment as well as procurement of spare parts for port heavy equipment. In 2018 along with improving the work performance of PT. XYZ expands its wings to civil works in the port sector, starting from dock repair work, maintenance of port accessories, construction of structures and reclamation. In a maintenance service company and the provision of spare parts for port heavy equipment, the company's inventory must be guaranteed. at each site PT. XYZ especially PT. X has a limited warehouse, so it must maximize the company's inventory. In the company's existing condition, the amount of inventory still exceeds the number of user requests which will accidentally fill their warehouse and will increase the Total Inventory Cost (TIC). With this problem, TIC depreciation will be carried out with a periodic review policy (R, s, S) and a periodic review policy with a consignment stock inventory system. Based on the above method, the original TIC amounted to Rp. 43,063,451 with the periodic review method of TIC amounting to Rp. 38,318,736 or decreased by 11% and if using the periodic review method with the inventory consignment stock TIC system, the amount was Rp. 36,987,546 or decreased by 13%.